2013
DOI: 10.1016/j.apacoust.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The development and application of the emotional dimensions of a soundscape

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies of full items can be used for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 22 publications
(30 reference statements)
3
129
0
5
Order By: Relevance
“…automotive product development, to enable them to most easily achieve this. Furthermore the use of tools such as emotional dimensions [21] will help to more strongly link interventions to positive soundscapes and to measures of health and wealth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…automotive product development, to enable them to most easily achieve this. Furthermore the use of tools such as emotional dimensions [21] will help to more strongly link interventions to positive soundscapes and to measures of health and wealth.…”
Section: Resultsmentioning
confidence: 99%
“…Through conducing a Principal Component Analysis, these perceptual dimensions can be reduced to a simple two dimensional graphical representation, with one dimension on the x-axis and another dimension on the y-axis. A specific study to define the principal emotional dimensions of a soundscape is reported by the authors in a separate paper within this issue [21], where it was proposed that "calmness" and "vibrancy" are the key emotional dimensions of an urban soundscape. The study went on to show how through listening studies, current and potential future soundscapes can then be compared on a scale based upon these positive dimensions, allowing target setting for proposed soundscapes and the benchmarking of existing soundscapes.…”
Section: Implementation Of the Frameworkmentioning
confidence: 99%
“…Yu and Kang propose that, within urban open spaces, some of an individual's social, demographic, and behavioural factors affect his or her evaluation of sound levels [12]. Cain et al found that two independent emotional dimensions of a soundscape related to its "Calmness" and "Vibrancy" [13]. Rychtarikova and Vermeir evaluated urban soundscape by the objective analysis of binaural sound recordings, and classified the sound samples collected in urban public into 20 soundscape categories [14].…”
Section: Introductionmentioning
confidence: 99%
“…They focus on controlling the negative sound which leads urban soundscape towards the "less unpleasant" without being more "pleasant" (Kawai & Yano 2002;Cain et al, 2013). Simply decreasing or eliminating negative sound can lead to anxiety and create other problems, besides being insufficient for the account of improving urban environment (Kang & Zhang 2010;Cain et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Planners or decision makers concerned with noise complaints and management often looked into reducing and eliminating negative sounds, rather than trying to enhance the value of positive sound (Raimbault & Dubois, 2005;Cain et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%